ON THE THREAT OF SUPPLIERS FOR THE ENGINEERING CONSULTING AND DESIGN SERVICES FIRMS - Gabriel Sorin STROE (Risk in Contemporary Economy, 2014)
In the case of companies from engineering consulting and design services industry the classic models of analysis (e.g. Porter's five forces for structural analysis) exhibit interesting aspects in comparison with the situation when applied to traditional services or industrial production firms, due to the distinctive characteristics of the industry. The purpose of this paper is to present a general overview of the engineering consulting and design industry also analyze different facets of the suppliers concept and their force and threat for the engineering services firms. The paper aims at analyzing the dual strategic role of aspecial type of suppliers for the engineering companies.